THE UNIVERSAL VERSUS THE PARTICULAR IN ECOFEMINIST ETHICS - Kao, Grace Y. (Journal of religious ethics, 2010)
While not a monolithic movement, ecofeminists are united in their conviction that there are important connections between the exploitation of both women and nature. They are internally divided, however, on the propriety of applying their theoretical claims and activist strategies across social contexts. This paper explores three debates within ecofeminism that largely turn on this universalist versus particularist tension: whether ecofeminist theorizing can adequately account for cultural variation; whether its common usage of essentialist rhetoric is productive or troubling; and whether resources for social activism could legitimately be culled from an assembly of heterogeneous and foreign sources. I conclude that the universalism of the women–nature connection can indeed be justified if perceived in multivalent ways, that “earthcare” or “ecomaternalist” discourse can be helpful in some contexts but harmful in others, and that selective retrieval of other cultures for the purposes of advocacy should not be ruled out as necessarily imperialistic or otherwise inappropriate.